Transport Waste Separation and Recovery Trajectory Judged Based on Dijkstra's Algorithm. Issue 1 (June 2020) - Sun, Yanbin; Shen, Penglin; Jiang, Huimin; Zhang, Yuehua; Guan, Jinqiu; Li, Lan
Abstract: Urban waste classification and recycling is an important research node in people's livelihood, which is related to the corresponding relationship between efficiency and quality. The optimization of the recycling transportation path means that the cost is less. In the process of garbage transportation classification and recycling, optimizing and merging the routes of garbage transportation based on Dijkstra's algorithm can optimize the shared transportation resources, to achieve the result of saving operating costs. The immediate transportation recycling event is planned as the path planning optimization. Multi-source multi-object and multi-path planning problems, and rehearse the optimization model of the total length of the transport path set without repeated paths. When the scale of the transportation and recovery network grows to a set value, it is difficult to achieve a theoretical solution by accurately calculating the optimal value of the model through an optimization algorithm. An optimal path set selection algorithm based on a random walk is feasible. The effectiveness and operability of the method are verified by small experiments and simulation experiments. The path is the shortest, and compared with the summation algorithm, it not only has high accuracy, but also has high execution efficiency.